2020
DOI: 10.24329/aspikom.v5i2.741
|View full text |Cite
|
Sign up to set email alerts
|

Google Trends and Information Seeking Trend of COVID-19 in Indonesia

Abstract: WHO has declared COVID-19 as a pandemic due to its rapid increase in cases outside China. COVID-19 has also affected a growing number of countries. However, the Indonesia government responded to the declaration in a not-serious manner, which has generated uncertainty circumstance among its public. This circumstance has driven people to consume information as much as they are possible to consume. This study aims to map out the trend of information-seeking concerning COVID-19 in Indonesia using Google Trends and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 19 publications
1
23
0
8
Order By: Relevance
“…Regarding questions on seeking information about COVID-19, the majority of respondents admitted that they often sought (through reading) information about the spread of this virus. This confirms the research conducted by Limlia and Pratamawaty regarding the acceleration search for messages about COVID-19 in Indonesia, especially after the government announces the health emergency (Limilia & Pratamawaty, Bona, 2020). This intense search for the information is understandable, considering the COVID-19 outbreak is a new issue but has a significant impact on aspects of people's lives, particularly social and economic.…”
Section: Media Usage To Seek Information About Covid-19supporting
confidence: 82%
See 2 more Smart Citations
“…Regarding questions on seeking information about COVID-19, the majority of respondents admitted that they often sought (through reading) information about the spread of this virus. This confirms the research conducted by Limlia and Pratamawaty regarding the acceleration search for messages about COVID-19 in Indonesia, especially after the government announces the health emergency (Limilia & Pratamawaty, Bona, 2020). This intense search for the information is understandable, considering the COVID-19 outbreak is a new issue but has a significant impact on aspects of people's lives, particularly social and economic.…”
Section: Media Usage To Seek Information About Covid-19supporting
confidence: 82%
“…Several studies examined the relationship between the announcement of the COVID-19 cases and the increased search for information about this pandemic. This condition occurs in several countries, such as the United States (Bento, I et al, 2020), Spain (Moreno, Lara, Fuentes, & Navarro, 2020), Singapore and South Korea (Kim et al, 2020), including Indonesia (Limilia & Pratamawaty, Bona, 2020). The results of all these studies indicate relatively positive information-seeking behavior about COVID-19 and efforts to acquire information about this pandemic.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
See 1 more Smart Citation
“…In another development, during the first quarter of 2020, countries around the globe have faced one of the worst pandemics (Limilia & Pratamawaty, 2020). There are various industries that are most affected by COVID-19, such as the service industry (hospitality/tourism) and the food and beverage sector, which sell their services onsite (Bayu, 2020;ILO, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Here, the COVID-19 pandemic has increased the trend of doing business through social media. With lockdowns initiated at various locations, there is an increase in the adoption of digital channels and the use of the internet around the globe (Eoin Daly et al, 2020;Limilia & Pratamawaty, 2020). A recent study by Google & Temasek (2020) also reported that the coronavirus had caused massive adoption of digital services among customers in Indonesia, estimated with over 37% new digital services consumers, where 90% of them will continue their digital habits post-pandemic.…”
Section: Introductionmentioning
confidence: 99%